2021
DOI: 10.1155/2021/8736288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Afatinib in the Treatment of Advanced Non-Small-Cell Lung Cancer with EGFR Mutations: A Meta-Analysis of Real-World Evidence

Abstract: Introduction. The purpose of this study was to explore the efficacy and safety of afatinib in advanced non-small-cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations based on real-world evidence. Materials and Methods. Eligible real-world studies were identified from PubMed, Cochrane Library, and Embase. Cochrane guidelines were used to assess the quality of included studies. Cochran’s Q test and I2 statistics were used for the heterogeneity analysis. Results. Twenty-five st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This is in keeping with afatinib’s effectiveness as first-line treatment in patients with EGFR -mutant advanced NSCLC, which has been well established in clinical trials and real-world studies ( 4 , 6 - 9 , 16 , 17 , 21 - 25 ). Afatinib also has a good tolerability profile but as some patients do experience gastrointestinal and cutaneous AEs, tolerability-guided dose reduction has been suggested ( 8 , 9 , 22 , 25 ). In our study, patients on lower doses of afatinib had lower discontinuation rate due to AEs than those on standard dose.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with afatinib’s effectiveness as first-line treatment in patients with EGFR -mutant advanced NSCLC, which has been well established in clinical trials and real-world studies ( 4 , 6 - 9 , 16 , 17 , 21 - 25 ). Afatinib also has a good tolerability profile but as some patients do experience gastrointestinal and cutaneous AEs, tolerability-guided dose reduction has been suggested ( 8 , 9 , 22 , 25 ). In our study, patients on lower doses of afatinib had lower discontinuation rate due to AEs than those on standard dose.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this is also consistent with the conclusion of the LUX-Lung3/6 trails. It should be noted that we did not stratify the oral dose of afatinib in our selected studies because a meta-analysis reported no diference between the efcacy of the 30-mg group and the 40-mg groups [21]. Te common AEs of afatinib include skin rash, diarrhea, loss of appetite, stomatitis, vomiting, fatigue, and paronychia.…”
Section: Discussionmentioning
confidence: 99%